Effect of the phosphate fertilizer with filter cake on soil microbial activity and phosphorous uptake in sugar cane - Saucedo Castillo, Orlando; de Mello Prado, Renato; Castellanos González, Leónides; Ely, Nahas; Silva Campos, Cid Naudi; Pereira Da Silva, Gilmara; Assis, Luis Carlos (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The objective of the work was to evaluate the effect of different doses of phosphate fertilizer with the addition of sugar cane industry filter cake on the soil microbial activity and soil and plant P concentration in sugar cane. The experiment was carried out in vegetation house at Jaboticabal, Brazil, in 2013, and the sugar cane seedlings variety "CTC 05"was used as tests plant. The experimental units were pots containing Hapludox. A completely randomized design was used, with factorial arrangement of 5x2 and three repetitions. The treatments were five phosphorus doses: 0, 50, 100, 200 and 400 mg dm-3 and two levels of filter cake (absence and presence). Soil respiration, acid phosphatase and dehydrogenase activity, soluble carbon, pH value, soil and plant P concentrations. There was interaction among doses of P and filter cake application for all the variables, except for the pH. The phosphate with the addition of filter cake increased the microbial activity, the value of the pH and the P concentration in the soil, being reflected in a higher accumulation of P in the seedling.